EFL students’ preferences on digital platforms during emergency remote teaching: Video Conference, LMS, or Messenger Application? - Fakhrurrazi M. Amin; Hanna Sundari (Studies in English Language and Education, 2020)
The use of technology in language learning has extensively expanded in line with the advancement of technology itself. However, the investigation into the implementation of video conferences, learning management systems, and mobile applications, particularly during the emergency remote teaching/the Covid-19 pandemic, is still lacking. This paper presents survey data from three groups of Indonesian EFL students using three different digital learning platforms: Cisco WebEx Meeting video conferencing, Google Classroom learning management system (LMS), and WhatsApp mobile messenger application. The purpose of the study was to determine the students’ preferences including their perception and point of views on using the platforms and application during the remote teaching situation. There were 140 EFL students from two universities/institutes in Jakarta and Aceh to take part as the participants. The instrument was a questionnaire based on criteria of CALL evaluation, and descriptive analysis using percentages and thematic analysis was applied. The findings show that the Cisco WebEx Meeting, Google Classroom, and WhatsApp gained highly positive agreement on all criteria. Specifically, the Cisco WebEx meeting got the highest scores on authenticity and meaning focus. Meanwhile, for GC and WhatsApp, the criteria on language learning potential, meaning focus and authenticity achieved the highest scores. Moreover, WhatsApp is the most preferred among others in meaning focus, learner fit, positive impact, and practicality.  However, the three digital platforms received the lowest score on a positive impact at each group-participant. It seemingly indicates that they thought the full online digital learning system they experienced during ERT is less preferable than face-to-face learning.